Ritual communication - Senft, Gunter 1952-; Basso, Ellen B. 1942- (Wenner-Gren Center international symposium series., 2009)
"This volume presents a new approach to "ritual communication" by an international group of scholars from a multidisciplinary and cross-cultural perspective, rich with empirical data and path breaking for future theorizing on the topic. The chapters show how ritual communication involves witnessing a future through the making of cultural knowledge. They show ritual communication to be a highly "self-oriented" multimodal process in which the human body, temporalization, and spatialized settings play crucial roles. Ritual communication encompasses both verbal and sensory attributes. It is in part dependent upon prior formulaic and repeated action, and is thus anticipated within particular contexts of social interaction. It is performed and therefore subject to evaluation by its participants according to standards defined by language ideologies, local aesthetics, contexts of use, and interpersonal relations. The authors here emphasize the variety of participatory and experiential aspects of ritual communication in contemporary African, Native American, Asian, and Pacific cultures. Among the forms covered are ritual constraints on everyday interaction, gossip, private and public encounters, political meetings and public demonstrations, rites of passage, theatrical performances, magical formulae, shamanic chants, affinal civilities, and leaders' ceremonial discourse. The book is ideal for students and scholars in anthropology and linguistic anthropology in particular"--Provided by publisher.